On centers for Generalized Abel Differential Equation - Amen, Azad I. (Sulaimani Journal for Pure and Applied Sciences, 2013)
A new condition is given for generalized Abel differential equation to have a center. We apply the results to some polynomial differential systems in the plane to find necessary and sufficient center conditions.
Keywords: Abel differential equation; center condition; planar polynomial vector field